Correlation of non-stress test with fetal outcome in term of Apgar score- a prospective observation study - Choudhary, Neeraj; Verma, Savitri; Gandhi, Sudha; Gour, Yukti; Kumari, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Non-stress test (NST) is a graphical recording of changes in fetal heart activity and uterine contraction along with fetal movement when uterus is quiescent. The objectives of antepartum fetal surveillance are to prevent fetal death and avoidance of unnecessary intervention. This study using NST as a tool for routine antepartum fetal surveillance was trying to catch up those fetuses who might be at risk in womb and provide prompt intervention in otherwise considered normal pregnancies without any obvious high risk factor thus giving the best outcome in mothers. Methods: The objective of this study was to evaluate the correlation of the non-stress test with fetal outcome in pregnancies from 37-42 weeks of gestation. This was a prospective observational study at Pannadhaya Rajkiya Mahila Chikitsalya Udaipur (Rajasthan) from February 2022 to July 2022. This study included 100 normal pregnant mothers from 37 weeks to 42 weeks who were subjected to NST. Results: The parameters of poor fetal outcome like Apgar score <7 at 5 minutes had increased incidences in the non reactive group. Conclusions: NST tells about acute fetal hypoxia and decision to delivery time can be made for those patients with fetal distress so that a major improvement in the outcome among parturient can be achieved with abnormal NST results. So This study suggested that the NST was found to be a good predictor of the healthy foetus even in normal pregnancies between 37-42 weeks of gestation and the probability of an adverse outcome such as poor Apgar score increases with a non reactive strip.